A perspective on the status of mathematics in India - K. R. Sreenivasan (CURRENT SCIENCE, VOL. 93, NO. 8, 25 OCTOBER 2007, 2007)
My intention here is to comment briefly on the present status of mathematics in India. I approach the task with some diffidence because my own mathematical knowledge is limited and I have lived for some thirty-three years outside India. Thus, the perspective can at best be partial. Please bear with me if you see flagrant errors of detail or substance